Study of cytotoxic Effects Alcoholic Nerium Oleander L. Extract on female Albino mice - Baghdad Science Journal (مجلة بغداد للعلوم)
This study involved the evaluation of Alcoholic extract of Nerium Oleander L. plant that have a promising anticancer cell. This extract was compared to the well known anticancer drug Cis – Platinum by utilizing an in vivo system in female Albino mice. The first direction was cytogenetically using the mitotic Index of bone marrow cells as a parameter for the cytotoxic effect of this extract. The second direction was enzymatical using a widely distributed enzyme GOT in the different organs of mice: Liver , kidney , spleen and lung . Animals were treated with three doses of Cis-platin , 50 , 200 and 350 Mg/mouse for three days . The same doses were used for the other extract . This study showed that the extract have a promising anticancer cell as could be seen from these effect on mitotic Index (MI) of mice bone marrow , (MI) decreased in animals treated with different doses of extract , mitotic index was reduced to 78% on day three in animals treated with 350 ?g/mouse . These effects were similar to the effect of Cis-platin at the same doses. Comparing the effect of this extract on GOT enzyme showed that Cis-platin was more effective on activating the spleen GOT enzyme of about 95% than the extract while the extract is more effective in Lung , The extract activated GOT enzyme activity in the all organs.